Bacillus licheniformis JF-22 to Control Meloidogyne incognita and Its Effect on Tomato Rhizosphere Microbial Community - Du, Jianfeng; Gao, Qixiong; Ji, Chao; Song, Xin; Liu, Yue; Li, Huying; Li, Chaohui; Zhang, Pengcheng; Li, Jintai; Liu, Xunli (Frontiers in Microbiology, 2022)
Meloidogyne incognita is one of the most destructive soil pests, causing serious economic losses in tomato production. Here, in vitro experiments demonstrated that Bacillus licheniformis strain JF-22 has the potential to prevent M. incognita infection. A pot experiment confirmed that B. licheniformis strain JF-22 isolated from tomato rhizosphere soil and planted in the tomato root-knot nematode disease area effectively prevented and controlled M. incognita, reducing its negative effect on tomato growth. Additionally, the composition of volatile substances secreted by B. licheniformis strain JF-22 was analysed using solid-phase microextraction and gas chromatography-mass spectrometry. We detected acetoin, 2,3-Butanediol, [R-(R*,R*)]-, and hexamethyl cyclotrisiloxane as the main components among these volatiles. Using MiSeq sequencing technology and bioinformatics, we analysed the influence of B. licheniformis strain JF-22 on the microbial community of the tomato rhizosphere. B. licheniformis strain JF-22 changed the composition of the microbial community; particularly, it significantly reduced the diversity of the fungal community. Furthermore, using the FUNGuild and PICRUSt databases, we predicted the effect of JF-22 on microbial community function. In conclusion, B. licheniformis strain JF-22 may be considered as a potential biocontrol agent against M. incognita.